Assessment of awareness and knowledge of oral potentially malignant disorders and oral cancer among accredited social health activist workers from randomly selected blocks of Thrissur District, Kerala, India: A cross sectional study - C Roma Davis; Jubin Thomas; S Akhil; Sujith Menon; Ani John Peter; Amal Raj (Wolters Kluwer Medknow Publications, 2024)
Introduction: Oral and oropharyngeal cancers are prevalent in the head-and-neck region, with global rates decreasing. However, in India, they are rising due to a lack of knowledge about risk factors and symptoms. The Indian government launched the National Health Mission to provide accessible, affordable, and reliable primary health care. Accredited social health activist (ASHA) workers can link health services to rural people. This study aimed to evaluate the awareness level among these workers about potentially malignant oral disorders and oral cancer (OC). Materials and Methods: A predesigned semi-structured questionnaire-based descriptive cross-sectional study was conducted among 150 voluntary ASHA workers from randomly selected blocks of Thrissur district, Kerala, to collect the data. Results: Our study showed that the majority of ASHA workers (82.3%) were aware of the role of tobacco in OC. A substantial portion of workers (88.4%) expressed that early detection of OC is possible at its initial stage. Less than 10% (7.5%) of all the ASHA workers were educated by dentists, whereas almost three-quarters (75.5%) of ASHAs preferred primary health center health practitioners as primary representatives for early OC detection, despite their being poorly trained in the early diagnosis and detection of OC. Conclusion: India has made progress in controlling malignancies but still lags in reducing OC mortality rates. Spreading knowledge of contributory agents and early detection methods through ASHA workers could reduce the incidence and mortality of OC. Including more dentists in the public health system and training ASHA workers on early OC detection can play a major role in reducing its incidence.